Analysis of the Input, Process, and Output Stages of Vocational Industrial Work Practice Education in Enhancing Vocational High School Students’ Work Competence in East Jakarta - Lutfi Hardiyanto; Romdanih Romdanih; Yuliwati Yuliwati (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study analyzes the implementation of the Industrial Work Practice (Prakerin) program using an Input–Process–Output (IPO) framework to improve the work competence of Vocational High School (SMK) students in East Jakarta. A qualitative case study approach was applied at SMK Islam PB Soedirman 2 Cijantung and SMK Era Pembangunan Umat Ciracas. Data were obtained from grade XII students, supervisors, and industry partners through in-depth interviews, observation, and documentation. The findings indicate that at the input stage, student readiness, pre-placement training, and strong school–industry partnerships support program success. At the process stage, structured supervision effectively improves both technical and soft skills, although placement mismatches and limited industry mentors remain challenges. At the output stage, 92% of students gained relevant competencies, and 75% felt ready to work. The study recommends improving competency-based placement, strengthening mentor capacity, and adopting digital monitoring. Overall, Prakerin significantly enhances students’ competence and work readiness.